(E)-1-[4-(Hexyloxy)phenyl]-3-(3-hydroxyphenyl) prop-2-en-1-one - Zainab, Ngaini; Siti Muhaini, Haris Fadzillah; Hasnain, Hussain; Ibrahim, Abdul Razak; Fun, Hoong-Kun (US National Library of Medicine National Institutes of Health, 2010)
There are two molecules in the asymmetric unit of the title compound, C21H24O3, in which the dihedral angles between the aromatic rings are 6.4 (1) and 7.0 (1)°. The enone moiety of both molecules adopts an s–cis configuration. In the crystal, intermolecular O—H⋯O and C—H⋯O interactions to the same acceptor O atom generate R 2 1(6) ring motifs and further C—H⋯O interactions generate R 2 2(8) ring motifs. Topologically, the R 2 1(6) and R 2 2(8) ring motifs are arranged alternately, forming [001] chains of molecules. The crystal structure is further stabilized by C—H⋯π interactions.